Temporal and Spatial Variability of Fungal Structures and Host Responses in an Incompatible Rust–Wheat Interaction - Sørensen, Chris K.; Labouriau, Rodrigo; Hovmøller, Mogens S. (Frontiers in Plant Science, 2017)
Information about temporal and spatial variability of fungal structures and host responses is scarce in comparison to the vast amount of genetic, biochemical and physiological studies of host-pathogen interactions. In this study we used avirulent wild type and virulent mutant isolates of Puccinia striiformis to characterize the interactions in wheat carrying yellow rust Yr2 resistance. Both conventional and advanced microscopic techniques were used for a detailed study of morphology and growth of fungal colonies and associated host cell responses. The growth of the wild type isolates was highly restricted due to hypersensitive response (plant cell death) indicated by autofluorescence and change in the shape of the affected plant cells. The host response appeared post-haustorial, but large variation in the time and stage of arrest was observed for individual fungal colonies, probably due to a delay between detection and response. Some colonies were stopped right after the formation of the primary infection hyphae whereas others formed highly branched mycelia. Hypersensitive response was first observed in host cells in direct contact with fungal structures, after which the defense responses spread to adjacent host cells, and eventually leading to encasement of the fungal colony. Several cells with hypersensitive response contained haustoria, which were small and underdeveloped, but some cells contained normal sized haustoria without sign of hypersensitivity. The growth of the virulent mutants in the resistant plants was similar to the growth in plants without Yr2 resistance, which is a strong indication that the incompatible phenotype was associated with Yr2. The interaction between P. striiformis and wheat with Yr2 resistance was highly variable in time and space, which indicates that general conclusions about host defense mechanisms should proceed with caution.